Peran Kepemimpinan Adaptif Dalam Mendorong Inovasi dan Kreativitas Tim: Studi Literatur - Fauziyah, Shofi Nur; Wulandari, Suci; P, Rionaldi Aditya; Anshori, Mochammad Isa (CV. Lenggogeni Data Publishing, 2024)
In the era of globalization, the business world often faces many challenges. Challenges that often occur in companies that consist of individuals with different cultural backgrounds. This diversity, can provide benefits in the form of various perspectives and ideas from each employee of the team. But it can also pose challenges in terms of communication and collaboration. In addition, the increasingly fierce competition between companies encourages teams to innovate in order to survive and excel in the market. To encourage team innovation and creativity, adaptive leadership plays an important role. Writing this article using a literature study (literature review), this method uses previous research that is reviewed. The results of the study of adaptive leadership are leadership that is able and intelligent to deal with situations in a diversity of events by developing creative solutions. leaders with adaptive qualities motivate their followers/subordinates to welcome new things, increase confidence in decision making and face challenging situations. Companies often experience many challenges both internally and externally. To face these challenges, a leader who is able to adapt and motivate his employees to be more confident in their opinions is needed. Through this, companies can increase innovation and creativity in competition between companies and can achieve the desired goals.